2012
DOI: 10.1039/c2ob26209f
|View full text |Cite
|
Sign up to set email alerts
|

Corrole isomers: intrinsic gas-phase shapes via traveling wave ion mobility mass spectrometry and dissociation chemistries via tandem mass spectrometry

Abstract: PAPERCorrole and four of its isomers with subtle structural changes promoted by exchange of nitrogen and carbon atoms in the corrole ring have been studied by traveling wave ion mobility mass spectrometry and collision induced dissociation experiments. Significant differences in shapes and charge distributions for their protonated molecules were found to lead to contrasting gas phase mobilities, most particularly for corrorin, the most "confused" isomer. Accordingly, corrorin was predicted by B3LYP/6-31g(d,p) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Utilizing more polar drift‐gases could potentially influence almost every application area where structural isomers are being investigated by TWIM‐MS and improved R p‐p is required. Studies have already demonstrated the beneficial results in using CO 2 as the TWIM drift‐gas . Based on our findings, the use of more polarizable drift‐gases improves R p‐p considerably for the isomers that differ in electrostatic surface potential, whereas isomeric pairs which electrostatic surface potential is only subtly different, R p‐p is not significantly affected.…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing more polar drift‐gases could potentially influence almost every application area where structural isomers are being investigated by TWIM‐MS and improved R p‐p is required. Studies have already demonstrated the beneficial results in using CO 2 as the TWIM drift‐gas . Based on our findings, the use of more polarizable drift‐gases improves R p‐p considerably for the isomers that differ in electrostatic surface potential, whereas isomeric pairs which electrostatic surface potential is only subtly different, R p‐p is not significantly affected.…”
Section: Resultsmentioning
confidence: 99%
“…In TWIM, ions are accumulated and periodically released into a stacked ring ion guide (T‐wave cell) where they drift under the action of a continuous train of transient voltage pulses applied to a pair of stacked ring electrodes that work as an ion mobility cell. We have used TWIM‐MS to separate and characterize geometrical isomers such as meta/para and cis/trans cationic ruthenates meso‐pyridylporphyrins, corrole isomers and isomeric disaccharides …”
Section: Introductionmentioning
confidence: 99%
“…[28,29] In TWIM, ions are accumulated and periodically released into a stacked ring ion guide (T-wave cell) where they drift under the action of a continuous train of transient voltage pulses applied to a pair of stacked ring electrodes that work as an ion mobility cell. We have used TWIM-MS to separate and characterize geometrical isomers such as meta/para and cis/trans cationic ruthenates meso-pyridylporphyrins, [30] corrole isomers [31] and isomeric disaccharides. [32] For glycosylated molecules, in which different and highly competitive coordinating sites are available for cation binding, several catiomers [3] with eventually similar cross sections and polarizabilities could be formed, and therefore, the determination of the site of cationization is particularly challenging.…”
Section: Introductionmentioning
confidence: 99%
“…He, N 2 , or CO 2 ), referred to as collision cross section (CCS), under the influence of a weak electronic field . Hence, IM provides specific information on structural conformation and is therefore currently used in several research areas and applications with a wide range from low molecular weight compounds up to mega Dalton‐sized biological structures including the rapid detection of chemicals in waste water and air, peptide and protein structure determination, pharmaceutical compound analysis, and studies on crude oil …”
Section: Introductionmentioning
confidence: 99%
“…[26,27] Hence, IM provides specific information on structural conformation and is therefore currently used in several research areas and applications with a wide range from low molecular weight compounds up to mega Dalton-sized biological structures including the rapid detection of chemicals in waste water and air, peptide and protein structure determination, pharmaceutical compound analysis, and studies on crude oil. [28][29][30][31][32][33][34][35][36][37] In the present study, travelling-wave ion mobility spectrometry (TWIMS) with nitrogen as drift gas interfaced to a quadrupoletime-of-flight (QqTOF) mass spectrometer was used to generate information on the conjugation site of stanozolol glucuronides observed in post-administration urine samples and authentic doping control specimens. Therefore, drift times of five different but structurally related known AAS glucuronides were determined, corresponding CCSs were calculated by means of modelling software tools (ORCA and MOBCAL) employing the data set of B3LYP/6-31G, [38][39][40][41][42] and a calibration curve for AAS glucuronides was created.…”
Section: Introductionmentioning
confidence: 99%